COVID-19 Isolation and Risk of Death in Cyprus Elderly People - Kyriazis, Marios; Mikellides, George; Pantelidakis, Heraklis; Polycarpou, Marina; Panayiotou, Barnabas (Frontiers in Medicine, 2021)
Social isolation is associated with a higher risk of morbidity and death in older people. The quarantine and social distancing measures due to Covid-19 imposed in most countries and particularly in Cyprus, aim to isolate individuals from direct contact with others. This has resulted in vulnerable older people being isolated at their places of residence for several months, while the recommendations for continuing lockdowns do not appear to be ending. The risk of death from causes other than those related to Covid-19 increases in such individuals and it is due to the effects of social isolation. We estimate that in the next years, there will be a significant increase in the death numbers of such older people in Cyprus. The health authorities must develop a program of support for these older individuals to include medical, social, physical and psychological elements. Examples of such support are given here.